Prywatne może być publiczne? Vouchery – najbardziej radykalna forma prywatyzacji amerykańskiej edukacji - Potulicka, Eugenia (Kultura-Społeczeństwo-Edukacja, 2013)
Privatization is the main theme of educational politics in XXI century. The idea of vouchers is connected with the believe, that if parents can use publicly funded vouchers to cover tuition at the school of their choice, schools will be forced to compete for paying customers and hence will have reason to improve. But those who believe that education is a part of the implicit social contract required for an e ective democracy place emphasis on a school system that is free, publicly funded and guided by democratic decisions rather than that the market ones. Against vouchers was even Chief Justice Earl Warren, who have said that the opportunity of an education is a right which must be made available to all on equal terms.